2013
DOI: 10.1177/0956797613492424
|View full text |Cite
|
Sign up to set email alerts
|

Synesthesia for Color Is Linked to Improved Color Perception but Reduced Motion Perception

Abstract: Synesthesia is a rare condition in which one property of a stimulus (e.g., shape) triggers a secondary percept (e.g., color) not typically associated with the first. Work on synesthesia has predominantly focused on confirming the authenticity of synesthetic experience, but much less research has been conducted to examine the extent to which synesthesia is linked to broader perceptual differences. In the research reported here, we examined whether synesthesia is associated with differences in color and motion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 31 publications
9
51
1
Order By: Relevance
“…The data indicate that synesthetes had reduced motion sensitivity (i.e., higher coherence thresholds) compared to non-synesthetes. A, B & D: adapted with permission [1]. …”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…The data indicate that synesthetes had reduced motion sensitivity (i.e., higher coherence thresholds) compared to non-synesthetes. A, B & D: adapted with permission [1]. …”
Section: Figurementioning
confidence: 99%
“…In a recent paper, Banissy and colleagues [1] examined whether color synesthesia influences basic feature level perception in the absence of inducing stimuli. They found that synesthetes who experience color as their evoked sensation (concurrent) are better at discriminating color than non-synesthetes.…”
mentioning
confidence: 99%
See 3 more Smart Citations